PENGARUH SUKU BUNGA TERHADAP PERTUMBUHAN EKONOMI:PENDEKATAN TIME SERIES - Anjeli Anjeli; Levia Saputri; Gustina Masitoh (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This study examines the impact of interest rates on economic growth in Indonesia using a time series approach. Interest rates play a significant role in determining the levels of investment and consumer spending, both of which are key factors in economic growth. Monthly secondary data from 2016 to 2021 were used to analyze this relationship through path analysis. The results show that low interest rates can stimulate economic growth by enhancing access to funding, while high interest rates tend to reduce economic activity. The relationship between inflation, interest rates, and economic growth is highly complex, with important implications for Bank Indonesia’s monetary policy. This study emphasizes the need for a deep understanding of the interaction among these three variables to formulate policies that support sustainable growth.